Answer:
-18
Explanation:
a - b
a = -7
b = 11
Insert -7 for 'a' and 11 for 'b'
-7 - 11
= -18
Answer:
1 i koow
Step-by-step explanation:
Answer:
a.p→¬q
b.¬p→¬q
c.q→¬p
Step-by-step explanation:
p:You drive over 65 miles per hour
¬p: <em>You do not drive over 65 miles per hour</em>
q:You get a speeding ticket
¬q:<em>You do not get a speeding ticket</em>
(a) You drive over 65 miles per hour, but <em>you do not get a speeding ticket</em>
the first sentence is p and because the consequence is the opposite of q then is no q
p→¬q
(b) If you do not drive over 65 miles per hour, then you will not get a speeding ticket
The first sentence is the opposite of p (¬p), and the second sentence is the opposite of q
¬p→¬q
(c) You get a speeding ticket, but you did not drive over 65 miles per hour.
The first one is q, and the second one is the opposite of p so
q→¬p